Efficacy and safety profile of 2-year netakimab treatment in patients with moderate-to-severe plaque psoriasis in terms of the randomized double-blind placebo-controlled BCD-085-7/PLANETA clinical trial - Andrey I. Bakulev; Alexey V. Samtsov; Evgeny V. Sokolovskiy; Muza M. Kokhan; Marianna M. Khobeish; Vladislav R. Khairutdinov; Arfenya E. Karamova; Olga U. Olisova; Dmitry V. Ignatiev; Aleksandra N. Nikiforova; Antonina V. Artemeva; Arina V. Zinkina-Orikhan (State Scientific Center of Dermatovenereology and Cosmetology, 2022)
Background. Netakimab, a recombinant humanized monoclonal antibody, specifically binding to IL-17 blocks its activity resulting in plaque psoriasis signs decrease. The results of the first year of BCD-085-7/PLANETA study showed high efficacy and a favorable safety profile in the treatment of patients with moderate-to-severe psoriasis. Aims. Efficacy and safety assessments of netakimab through 2 years of treatment in patients with moderate-to-severe psoriasis. Materials and methods. BCD-085-7/PLANETA study is ongoing Randomized, Double-blind, Placebo-Controlled Phase III clinical study. In the study, 213 patients with moderate-to-severe plaque psoriasis were randomly assigned to one of three study groups. In the first two groups of patients, after weekly drug administration, received netakimab at a dose of 120 mg every two or four weeks. In the third group the patients received placebo. During 12-week double-blind study period the efficacy were evaluated based on the proportion of patients achieved PASI 75. After that all patients were switched to netakimab (once in 4 weeks). Patients who failed to achieve PASI 75 at Week 52 were withdrawn from the study. The open period lasts about 3 years. Herein we focus on the results of 2-year netakimab treatment (120 mg, weekly for 3 weeks, then once in 4 weeks), the recommended per label dose. Taking into account the epidemiological situation (COVID-19) and results limitation due to missing visits, additionally to the efficacy analysis in patients received, at least, one dose of netakimab, analysis in those of them who had relevant data on each visit per Protocol was conducted (ITT and PP populations). Results. At Year 1, PASI 75/90/100 responses were achieved in 88,7/74,5/56,6% patients, respectively (ITT-population) and in 100/85/66% patients, respectively (ITT-population). In 2 year, 69,3/58,0/40,6% sustained their responses in ITT-population and 93,2/78,2/53,1% in PP-population. Through 2 years, the high quality of life sustained among patients. The safety profile remained favorable and immunogenicity was low. Conclusions. Treatment with netakimab at a dose of 120 mg every 4 weeks results in high rates of sustained clinical response and quality life improvement in patients with moderate-to-severe plaque psoriasis with remains of a favorable safety profile.